(untitled) (Bangladesh Journal of Medical Microbiology, 2013)
Recently non-fermenting Gram negative rods (NFGNR) are playing an important role in healthcare associated infections. This observational study in a tertiary care hospital of Dhaka city conducted during 01August 2007 to 30 June 2013 found that 34.8% isolated organisms from patients with healthcare associated infections were NFGNR. Majority (74.3 %) of these infections were occurring inside critical care areas. Pseudomonas and Acinetobacter together constituted 79.6% of the total NFGNR whereas Burkholderia cephacia complex (15.4%), Stenotrophomonas (4.3%) and Chryseobacterium species (0.7%) combined constituted remaining 20.4%. Out of total NFGNRs, Pseudomonas was responsible for highest number of catheter associated urinary tract infections (55.6%), ventilator associated pneumonia (46.3%), respiratory tract infection (65.8%) and surgical site infection (70.6%). Blood stream infection was predominantly caused by Burkholderia cephacia complex (33.5%) and Acinetobacter spp. (39.5%). Other than colistin most of the organisms were resistant to antibiotics commonly recommended for NFGNR. DOI: http://dx.doi.org/10.3329/bjmm.v7i2.19326 Bangladesh J Med Microbiol 2013; 07(02): 6-12